Nauka prawa w sztuce filmów animowanych - Ostrowski, Piotr (Strategie komunikacyjne i procesy twórcze, 2022)
This paper deals with the analysis of legal content in animated films. The study covers both the presence, functioning and role of legal aspects in these pieces and the possibility of their use in the process of legal education. The analysis is conducted on the basis of the ten most lucrative animated movies in the history of cinema, which were released until 2017. The author points out the structuring role of law in animated movies and notes that the plot of the film in many cases develops due to the occurrence of legal events, and the motivations of the characters' actions are often determined by incentives to achieve the desired legal consequences. The article emphasizes that the law is treated in animated movies as a means to achieve certain goals, for example, humoristic or regarding developing plot, as evidenced by the differences in the translation of dialogues involving legal issues into different languages. At the same time, the author draws attention to the practical possibilities of using animated films in the process of legal education of children.